A Study of Spatial Inequality in Blitar (Area: Facilitating Worse-off People to Develop) - Nurâ€™aini, Nurul (Magister Pembangunan Wilayah dan Kota,Undip, 2012)
Spatial inequality is understood as the disparity among spatial units in a region perceived by the people. Some spatial units can provide proper and affordable public facilities and infrastructure while some others cannot. In Blitar region, spatial inequality is apparent between the North and South part of the region. In this case, the worse-off people (WOP) suffered the most from the situation. Brantas River stretching east-west in the region, marks the boundary dividing the territory into two parts: the North and South sub regions. So far, the North part appeared to be more developed than the South. This study was aimed to answer the question â€œhow to facilitate the worse-off people to get more equitable benefits from the regional developmentâ€. The study examined seven aspects of development, i.e. employment, income taxes, minimum wages, social security, educational services, health services and basic infrastructure. The study employed random sampling survey to the WOP of Blitar region, in proportion to the district units (kecamatan). Questionnaires provided perceptions from the WOP per household unit. The study found that the WOP living in the North do not always feel better than those in the South. The North WOP are better in terms of taxation, minimum wages and educational services, while the South WOP are better in the aspects of employment, health services and basic infrastructure. Policy implication analysis recommended immediate reformulations of two policies regarding employment and basic infrastructure, especially clean water and electricity.